Influence of sulfate and the interactions of major organic and inorganic solutes on the formation of nitrite during VUV photolysis of nitrate-rich water. Issue 4 (August 2021) - Han, Mengqi; Mohseni, Madjid
Abstract: Vacuum ultraviolet (VUV) irradiation, is an effective process for degrading micropollutants in water. However, its wide scale applications are affected by the potential formation of nitrite during irradiation of nitrate-containing water. Through detailed experimental and mechanistic studies, this paper investigated the effects of sulfate along with other major organic and inorganic solutes such as natural organic matter (NOM) and chloride on nitrite formation. Sulfate, at environmentally relevant concentrations, showed little impact. However, when sulfate present at higher concentrations (e.g., 300 mg/L of SO4 2- –S), it led to reduced nitrite formation. Using UV254 /persulfate process as control, it was established that sulfate radical (SO4 - ) which is formed at initial sulfate reacts with nitrite, to reform nitrate. Besides sulfate, NOM and chloride have each affected the formation of nitrite in the solution. NOM at 6 mg/L resulted in 200% increase in nitrite formation, whereas 30 mg/L chloride led to 50% lower nitrite formation. Of all the solutes tested in this study, NOM showed to be the most dominant solute to increase nitrite formation, indeed it rendered the roles of other solutes insignificant. When degrading carbamazepine (CBZ), as model micropollutant, sulfate radicals formed during the VUV process showed to improve the degradation efficiency without increasing nitrite formation. Graphical Abstract: ga1 Highlights: The effect of sulfate is only pronounced at extremely high concentration. Sulfate radical can convert nitrite to nitrate, resulting in reduced nitrite formation. Presence of NOM and chloride diminish the impact of sulfate on nitrite formation. Sulfate radical can increase the degradation efficiency of micropollutant carbamazepine. NOM is the most dominant solute in terms of influencing nitrite formation.